HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA ARAB PADA MATA KULIAH NAHWU: Abstrak, pendahuluan, metode penelitian, hasil, kesimpulan, referensi - Sarah Mutia (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
This research is a type of quantitative research that aims to determine whether or not there is a correlation between learning motivation and learning outcomes of Arabic language education study program students in nahwu courses. Data collection techniques through observation and distribution of questionnaire statements to 23 samples. The sampling technique used a random sample technique, with a population of 6th semester Arabic language education students. The results showed that student learning motivation in nahwu courses was categorized as high with an average value of 82.9, as well as student learning outcomes with an average value of 84.2. By using the product moment correlation formula, it can be concluded that there is no strong correlation between learning motivation and learning outcomes of Arabic language education study program students in nahwu courses, because the table correlation coefficient is greater than the calculated correlation coefficient (rtabel≥ rcount = 0.433≥ 0.133), with a coefficient of determination of 0.02, meaning that learning motivation contributes 2% to student learning outcomes.